SEARCH ENGINE MARKETING A NEW WAY OF MARKETING IN DIGITAL AGE - Bijay Prasad Kushwaha (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Search engine has become very strong tool for digital marketers because of internet user habitual behaviours. Most of the users begin their surfing with search box of search engine. Therefore, digital marketers are putting efforts to pull target audience from search engine result page. This paper investigates the mediating role of website optimisation for successful search engine marketing. This papers has taken keyword search as an independent variable, website optimisation as mediating variable, and search engine marketing as dependent variable. The convenience sampling technique was used to interview 367 respondent of Punjab, India. This finding suggest that keyword search plays vital role in the success of search engine marketing however, if website optimisation is done properly with the help of popular keyword then the effectiveness of search engine marketing increases. SPSS AMOS was used to analyse collected data and to reach specific conclusion.